Clinical characteristics of 9 cancer patients with SARS-CoV-2 infection - Yong Zeng; Bo Zhang; Xufeng Zhang; Cunjian Yi (BMC, 2020)
Abstract In December 2019, a cluster of pneumonia cases was caused by the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) in Wuhan, China. Cancer patients are a special group, the immunity of them will be suppressed because of various anti-tumor treatments, and the risk of infection will be greatly increased, so we will report clinical features of 9 cancer patients with SARS-CoV-2 infection. 5 (56%) patients were ordinary type, 3 (33%) were severe type, and 1 (11%) was critical type. A total of 8 patients received combined therapy of traditional Chinese medicines and western medicines. From the clinical outcomes of these 8 patients, western combined therapy of traditional Chinese medicine was indeed an effective treatment method. D-dimmer rise, infection index rise, and chest CT(computed tomography) progression may be clinical warning indicators for severe patients, in our study, more 50% of patients had elevated levels of these indicators, but only 44% (including the dead) of patients had received treatment in the intensive care unit. 5 (56%) ordinary type patients had been discharged, while the 1 (11%) critical type patient died 3 days after admission. Cancer comorbidity seems to have no direct relationship with severe events, and the combination of traditional Chinese medicine and western medicine may be effective in the prevention and treatment of novel coronavirus-infected pneumonia (NICP).